100 questions & answers about pancreatic cancer - O'Reilly, Eileen M.; Kelvin, Joanne Frankel (Sudbury, Mass. : Jones and Bartlett Publishers, 2010)
Answers one hundred common questions about pancreatic cancer, covering symptoms, diagnosis, treatment options, quality of life, and other topics
Part 1 The Basics 1 -- Part 2 Diagnosis and Staging 15 -- Part 3 Treatment 25 -- Part 4 Managing Your Treatment 71 -- Part 5 Changes Cancer Brings 85 -- Part 6 Emotional and Social Concerns 127
Includes bibliographical references and index
13
Keywords: Pancreas -- Cancer -- Miscellanea; Pancreas -- Cancer -- Popular works; Pancreatic Neoplasms -- Popular Works